Dodabetta Medicinal Plant Development Area in Nilgiris - an Experience in Rehabilitation - Sekar, T. (Indian Forester, 2004)
The decline in demand for quinine sulphate, the prime anti malarial drug and the major product of Cinchona Department necessitated the closure of the Department by 1990, thus, among other things, forcing the 40 odd worker families at Dodabetta farm, Nilgiris to go suddenly jobless. Tamil Nadu Forest Department through its Nilgiris North Forest Division in association with Health for People and Environment (HOPE) initiated the process of rehabilitation, of these worker families by involving them in developing a medicinal plants production programme with the finaneial support from Foundation for Revitalization of Local Health Traditions (FRLHT), Bangalore. Over the last seven years since 1995 the local community gradually built up the MPDA area ineluding land development, establishment of medicinal plant nursery, plantations, harvest, post harvest techniques, extraction of oil, its packaging and marketing. Besides providing the members with guaranteed employment, the Dodabetta MPDA is maintaining the revenue generation and profit thus indicating that the programme is moving towards sustainability. The community also promoted group activities like formation of Self Help Groups, which are built around thrift and credit. As a consequence of the programme, perceptible improvement in the economic status of the members of the village committee is visible.